Effects of Noticing Model Texts Using the Translanguaging Approach on L2 Learners' Syntactic Awareness in Multimodal Texts - Nurul Atikah, Mustafa; Wan Jumani, Fauzi (2022)
Writing is challenging for any ESL learner, even at tertiary level. This study investigated the effects of noticing model texts using the translanguaging approach on L2 learners' syntactic awareness in multimodal texts in a private college in Malaysia. This mixed method case study employed a pretest-posttest design to measure participants’ writing performance before and after the intervention, which involved the participants to work collaboratively to produce multimodal texts on Instagram based on selected eight-picture stories in two phases. In both phases, participants had to compare their multimodal texts with a model text employing the translanguaging approach to discuss the similarities and differences of the texts in group chats on Instagram and then, renarrate another eight-picture story. All the texts went through error analysis and the Instagram chats underwent content analysis. Findings revealed that the noticing of model texts using the translanguaging approach in Instagram chats helped the participants in heightening their syntactic awareness which was evident in the writing improvement of the group tasks but not as obvious in individual writing performance. This study is significant because it shows that using model texts for students to notice linguistic features through comparison with their own writing empowers them to be more student-centered and the texts act as a scaffold for the students to assist one another to learn the target language. Future studies are recommended to include individual multimodal writing tasks in the intervention to reduce participants’ reliance on ‘more knowledgeable others’ and internalize syntactic awareness better on their own.